Pengetahuan, Sikap, Sarana, dan Petugas Kebersihan dengan Perilaku Dalam Pengelolaan Sampah Plastik - Sulistiyorini, Desy (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Plastic waste is still a global problem that has not been resolved to date. Indonesia produces 68.5 million tons of waste in 2021. Of this amount, around 17% or around 11.6 million tons is plastic waste. This research aimed to determine the relationship between knowledge, attitudes, availability of infrastructure, and cleaning staff with plastic waste management behavior in Purwasari Village, Dramaga District, Bogor Regency. A quantitative research method with a cross-sectional research design was used. The sampling technique was carried out using purposive sampling with 37 respondents with a total eligible sample of 16 respondents. The research results show that there is relationship between knowledge (p-value=0.039), attitudes (p-value=0.007), the availability of infrastructure (p-value=0.012), cleaning staff (p-value=0.003), and plastic waste management behavior. Based on the findings from the results of this research, it is hoped that there will be initiation of improvements to waste management facilities and facilities. Apart from this, there is also a need for outreach and assistance activities for the community regarding plastic waste management to increase community knowledge and attitudes in managing plastic waste